Tuning Oleophobicity of Silicon Oxide Surfaces with Mixed Monolayers of Aliphatic and Fluorinated Alcohols - Lee, Austin W H (Langmuir : the ACS journal of surfaces and colloids, 2016)
We demonstrate the formation of mixed monolayers derived from a microwave-assisted reaction of alcohols with silicon oxide surfaces in order to tune their surface oleophobicity. This simple, rapid method provides an opportunity to precisely tune the constituents of the monolayers. As a demonstration, we sought fluorinated alcohols and aliphatic alcohols as reagents to form monolayers from two distinct constituents for tuning the surface oleophobicity. The first aspect of this study sought to identify a fluorinated alcohol that formed monolayers with a relatively high surface coverage. It was determined that 1H,1H,2H,2H-perfluoro-1-octanol yielded high quality monolayers with a water contact angle (WCA) value of ∼110° and contact angle values of ∼80° with toluene and hexadecane exhibiting both an excellent hydrophobicity and oleophobicity. Tuning of the oleophobicity of the modified silicon oxide surfaces was achieved by controlling the molar ratio of 1H,1H,2H,2H-perfluoro-1-octanol within the reaction mixtures. Surface oleophobicity progressively decreased with a decrease in the fluorinated alcohol content while the monolayers maintained their hydrophobicity with WCA values of ∼110°. The simple and reliable approach to preparing monolayers of a tuned composition that is described in this article can be utilized to control the fluorocarbon content of the hydrophobic monolayers on silicon oxide surfaces